A DC Programming Approach for Sensor Network Localization with Uncertainties in Anchor Positions - Wu, Changzhi; Li, C.; Long, Q. (American Institute of Mathematical Sciences, 2014)
The sensor network localization with uncertainties in anchor positions has been studied in this paper. We formulate this problem as a DC (difference of two convex functions) programming. Then, a DC programming based algorithm has been proposed to solve such a problem. Simulation results obtained by our proposed method are better performance than those obtained by existing ones.